2017
DOI: 10.1007/s10571-017-0478-0
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Homocystinuria Due to Cystathionine ß-Synthase Deficiency: Findings in Patients and in Animal Models

Abstract: Homocystinuria is an inborn error of amino acid metabolism caused by deficiency of cystathionine ß-synthase (CBS) activity, biochemically characterized by homocysteine (Hcy) and methionine (Met) accumulation in biological fluids and high urinary excretion of homocystine. Clinical manifestations include thinning and lengthening of long bones, osteoporosis, dislocation of the ocular lens, thromboembolism, and mental retardation. Although the pathophysiology of this disease is poorly known, the present review sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 42 publications
1
27
0
1
Order By: Relevance
“…Oxidative stress may play an important role in the pathophysiology of homocystinuria, as deduced from studies carried out in patients and animal models [ 129 ]. Protein, lipid, and DNA oxidative damage and decreased antioxidant defences have been found in patients [ 130 132 ].…”
Section: Homocystinuriamentioning
confidence: 99%
“…Oxidative stress may play an important role in the pathophysiology of homocystinuria, as deduced from studies carried out in patients and animal models [ 129 ]. Protein, lipid, and DNA oxidative damage and decreased antioxidant defences have been found in patients [ 130 132 ].…”
Section: Homocystinuriamentioning
confidence: 99%
“…While the value of reproducibility is well recognized, few such studies occur in rare diseases. For instance, in a recent review of oxidative stress and inflammatory markers studies in CBSDH three of six publications were by the same author involving a common cohort at a single service . All studies had a small number of subjects.…”
Section: Discussionmentioning
confidence: 94%
“…Previous work has reported that vitamin C therapy, an antioxidant, ameliorated endothelial vascular dysfunction assessed as brachial artery endothelium‐dependent flow‐mediated dilation (FMD) in CBSDH . Human studies have implicated oxidative stress and inflammation as candidate pathogenic mechanisms in CBSDH. Similar findings were reported in mouse models of CBSDH.…”
Section: Introductionmentioning
confidence: 99%
“…. Patients with both primary hypertension and hyper homocysteine are known as having H‐type hypertension. Enneman et al .…”
Section: Discussionmentioning
confidence: 99%